Analysis of Customer Satisfaction with Marketing Services Using Fuzzy Logic - Alifah, Nurli; Fahmi, Hasanul (Asosiasi Doktor Sistem Informasi Indonesia, 2024)
In sales companies, the acquisition of turnover every month is very influential on the assessment of sales quality. The problem faced by the company is a decrease in turnover, this may be caused by the performance of marketing services, therefore the purpose of this study is to evaluate the service performance of the marketing team at Jayaindo Abadi Makmur. To improve customer satisfaction, the team should consider components such as reliability, responsiveness, assurance, and empathy. To get the results, mamdani fuzzy logic is used with the stages of fuzzy set, implication function, rule composition, and affirmation (deffuzzy). The results showed that customer satisfaction with manual calculations amounted to 84.12, while the results with mamdani fuzzy logic using matlab software amounted to 81.3. The company's customer satisfaction is classified as very satisfied. Sales quality shows a decrease in turnover several times, but this is not caused by the marketing team. Recommendations for improvements that can be made include improving product management, pricing policies, and overcoming market competition. The data presented shows that the company's ability to manage products, pricing policies, and the competitive market atmosphere can contribute to higher levels of customer satisfaction.